Pengaruh Konseling Realitas terhadap Peningkatan Percaya Diri (Indo-MathEdu Intellectuals Journal, 2026)
This study aimed to examine the effect of reality counseling on improving self-confidence among eleventh-grade students at SMK Negeri 2 Gunungsitoli in the 2024/2025 academic year. A quantitative approach with a quasi-experimental pretest–posttest control group design was employed. The population consisted of 80 students, and 30 students were selected using purposive sampling based on low self-confidence criteria, then assigned into experimental and control groups (15 students each). Data were collected using a 30-item Likert-scale questionnaire that met validity (Pearson Product Moment) and reliability (Cronbach’s Alpha) requirements. The procedure included pretesting, implementation of reality counseling intervention for the experimental group, and posttesting for both groups. Data analysis involved normality, homogeneity, and Independent Sample t-Test at a 0.05 significance level. The findings revealed a significant difference between groups (p < 0.05), with higher posttest mean scores in the experimental group. These results confirm that reality counseling is empirically effective in enhancing students’ self-confidence and can serve as a strategic school counseling intervention.